Abnormal shadow contrast imaging for optimal objective lens condition in transmission electron microscope - Yong-Eun Kwon; Cheolsu Han; Sang-Chul Lee; Jong-Man Jeung; Gaehang Lee; Tae-Yeoung Lee; Jin-Gyu Kim (Journal of Analytical Science and Technology, 2022)
Abstract Background In a transmission electron microscope (TEM), the objective lens (OL) is the most important component because the first image and diffraction pattern for a specimen are formed by applying a specific OL current and specimen height (SH). In TEM, the focal length of the OL should be controlled independently of the specimen position. Therefore, the initial conditions for OL should be determined by selecting the optimum imaging condition of the specimen based on the OL current and the specimen position. We would like to present a method for finding the optimal imaging condition for OL that can be applied to conventional or low-resolution TEM where high-resolution (HR) imaging is impossible. Findings We conducted an abnormal contrast imaging experiment using Au nanoparticles (AuNPs). Abnormal contrast imaging was obtained by artificially controlling the mechanical alignment of OL P/Ps. Abnormal contrasts (shadow contrasts) of AuNPs were observed in all images obtained for various SH and OL currents. It was confirmed that these shadow contrasts of AuNPs result from the parasitic aberration caused by imperfect mechanical alignment of the OL P/Ps. From the quantitative analysis of the images, it was found that the effects of parasitic aberration in the TEM images decreased as SH approached the optimal position in the OL P/P. Conclusion We examined the relationship of SH and OL current using the abnormal contrast imaging technique. The standard OL current and optimal SH were determined with OL condition minimizing the shadow contrast of images. The experimentally determined optimal SH at standard OL current in our specially designed OL system differed from that of the well-known asymmetry OL system. Therefore, it is essential to examine the optimum conditions from a practical perspective. Consequently, our abnormal contrast imaging method, which can be analyzed even in conventional imaging without HR-TEM performance, can help optimize the OL conditions during the manufacturing stage of the TEM instrument.